(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2023)
The research was conducted at the University of Baghdad/ Jadiriyah Complex from February to August 2021 and data was collected from 6 consulting offices as well as 5 research centers. Baghdad University/Jadiriyah Complex is a combination of traditional university and research university through their available advisory offices and research centers whose primary duty is to research and study according to a pre-prepared annual plan, both of which provide services and advice to the public and private sectors. as well as laboratories and clinics serving students, researchers and citizens at nominal wages, Research and studies carried out by researchers for the purpose of obtaining scientific promotion, changing scientific titles, etc., as well as supervising graduate research, some of which are solutions to problems in the public and private sectors. Through research sources, there has been a clear lack of cooperation between State ministries, their departments and the private sector with advisory offices and scientific research centers within the University/ Jadiriyah Complex, although they are accredited by the Ministry of Higher Education and Scientific Research and related bodies. There was also a weakness in terms of information for the purpose of informing citizens of the services provided by the above offices and centers, as well as in terms of the remuneration of examinations and consultations, where there was a difference between them and the offices of the private sector, which were similar to the government advisory offices, as well as the specialization of a consulting office. (Advisory Office of the Centre for Urban and Regional Higher Education Planning) in urban planning, which is not similar in operation at the University of Baghdad but in Iraq, as well as one of the research centers The Market Research and Consumer Protection Center is the only center at the University and in Iraq specializing in market research and studies and consumer protection.